Co-Production of Polysaccharides and Platform Sugars from Wheat Straw Fermented with Irpex lacteus - Pu, Jun; Huhe, Taoli; Ding, Xiao; Yuan, Ruling; Zhang, Sainan; Ren, Jianjun; Niu, Dongze (Sustainability, 2025)
Sustainable valorization of lignocellulosic biomass, such as wheat straw (WS), into valuable products is key for efficient resource utilization. This study investigated an integrated strategy combining Irpex lacteus fermentation with subsequent alkali extraction to improve WS valorization. Alkali extraction parameters, including sodium hydroxide concentration, solid-to-liquid (S:L) ratio, temperature, and time, were optimized based on polysaccharide yield and purity. Optimal conditions were identified as 0.8 mol/L sodium hydroxide, a 1:25 S:L ratio, 90 °C, and 1 h, yielding 6.63% polysaccharides with 52.01% purity. Compared to untreated straw, the combined fermentation and alkali extraction treatment significantly altered the WS residue’s composition and structure, substantially reducing hemicellulose and acid detergent lignin while consequently increasing relative cellulose content. This enhanced cellulose accessibility resulted in a markedly improved glucose yield upon enzymatic hydrolysis, reaching 586 g/kg dry matter for the residue after combined treatment. Demonstrating a strong synergistic effect, this yield represents a 5.42-fold increase compared to untreated WS and a 3.30-fold increase compared to solely fermented straw. Analyses of SEM, FTIR, and XRD confirmed that the integrated treatment effectively disrupted the lignocellulosic structure by removing lignin and hemicellulose. This created a more porous morphology and increased cellulose exposure, which was deemed more critical for hydrolysis than the observed 18.58% increase in the cellulose crystallinity index relative to untreated straw. Thermogravimetric analysis further reflected these structural and compositional changes through altered thermal decomposition profiles. Therefore, integrating polysaccharide extraction with fungal fermentation is a highly effective strategy for improving resource efficiency in WS valorization. This approach enables the efficient co-production of valuable polysaccharides alongside significantly boosted platform sugar yields, offering a promising route towards more economically viable and sustainable WS utilization.